FEATURES OF CD 68 RECEPTOR EXPRESSION IN THE SEROUS GLANDS OF THE FRONTAL SINUS MUCOSA - Dovbnya, Y.N.; Pronina, E.N.; Yeroshenko, G.A. (World of Medicine and Biology, 2016)
The investigation presents an analysis of immunohistochemical localization and degree of expression of the integral transmembrane glycoprotein CD 68 in the lamina propria of human frontal sinus mucosa. Installed very strong level of expression of the free macrophages marker, which are diffusely localized in the connective tissue and surrounds the end-pieces and ducts. Surprisingly founded stable (in all walls of the frontal sinus with a decrease by 3 to 1 points, respectively, on the lower, front and posterior walls) expression of CD 68 in the cytoplasm of the serocytes of end-pieces. Very weak secretion response in the lumens of excretory ducts confirms findings by the end-pieces.
Keywords: human frontal sinus; CD 68; macrophages; glands